Didactics of smart pedagogy : smart pedagogy for technology enhanced learning - Daniela, Linda, 1967- (Cham : Springer International Publishing : Imprint: Springer, 2019)
The focus on smart education has become a new trend in the global educational field. Some countries have already developed smart education systems and there is increasing pressure coming from business and tech communities to continue this development. Simultaneously, there are only fragmented studies on the didactic aspects of technology usage. Thus, pedagogy as a science must engage in a new research direction-smart pedagogy. This book seeks to engage in a new research direction, that of smart pedagogy. It launches discussions on how to use all sorts of smart education solutions in the context of existing learning theories and on how to apply innovative solutions in order to reduce the marginalization of groups in educational contexts. It also explores transformations of pedagogical science, the role of the educator, applicable teaching methods, learning outcomes, and research and assessment of acquired knowledge in an effort to make the smart education process meaningful to a wide audience of international educators, researchers, and administrators working within and tangential to TEL.
Chapter1: Principles of Teaching and Learning in the Context of Smart Pedagogy -- Chapter2: Learning Theories in Context of Smart Pedagogy -- Chapter3: Cognitive Development in the Context of Smart Pedagogy -- Chapter4: Knowledge Construction Principles -- Chapter5: Motivation -- Chapter6: Sensor (Motor) Development in Smart Learning Environments.
Includes bibliographical references and index.
Keywords: Educational technology; Learning; Instruction; Education-Data processing; Assessment; Assessment, Testing and Evaluation